THE USE OF IRONY IN 20TH CENTURY AMERICAN LITERATURE (Modern education and development, 2024)
The article on "The Use of Irony in 20th Century American Literature" explores the significance and evolution of irony as a literary device in the works of key American authors during the 20th century. It examines how irony functions to critique social, political, and cultural issues, often reflecting the complex, disillusioned nature of modern life. Through the analysis of works by writers such as F. Scott Fitzgerald, Ernest Hemingway, and John Barth, the paper discusses how irony is used not only for humor but also as a tool for deeper commentary on the human condition, existential struggles, and societal norms. The study highlights the diversity in the use of irony, from subtle to overt, and its role in shaping narrative structures and reader perception.